Inter-rater and test-retest reliabilities of lumbar stiffness measurement in the postero-anterior direction using a portable algometer and the Kinovea program - Yodchaisarn, Wantanee; Rungruangbaiyok, Sunthorn; de Lourdes Pereira, Maria; Rungruangbaiyok, Chadapa (PeerJ, 2023)
Background Back pain negatively impacts a person’s quality of life and can cause major disability or even death. The measurement of spinal stiffness can be utilized as a promising tool to guide therapeutic decisions regarding physical therapy that result in effective back pain management. This study aimed to determine the reliability of instrumented postero-anterior (PA) stiffness assessment of the lumbar spine in asymptomatic participants by novice assessors using a portable algometer and the Kinovea program. Methods Thirty asymptomatic participants aged 18–25 years were enrolled in this study. Two novice assessors examined the participants for lumbar spinal stiffness at L1–L5 for two consecutive days. The algometer was applied to measure the PA force that applied to each lumbar. The stiffness assessment of each lumbar region was recorded as a video. The 600 data sets of assessment videos were imported into the Kinovea program to perform displacement measurements of each lumbar level. Spinal displacement values at 15 N were defined by graph plotting between force and displacement. The spinal stiffness values were defined by slope calculation. Both variables were analyzed for inter-rater and test-retest reliabilities using intra-class correlation coefficients (ICCs) and standard error of measurement (SEM). Bland-Altman analysis was applied to assess the inter-rater and test-retest systematical bias and limits of agreement of measuring displacement and stiffness. Results The inter-rater reliability of measuring the displacement and the stiffness of L1–L5 was moderate to good (displacement ICCs: 0.67–0.83, stiffness ICCs: 0.60–0.83). The test-retest reliability of measuring the displacement and stiffness of L1–L5 were moderate to good, ICCs: 0.57–0.86 and ICCs: 0.51–0.88, respectively. The inter-rater analysis’s Bland-Altman plot showed that the systematic bias was 0.83 when measuring displacement and 0.20 when measuring stiffness and the bias of both parameters were in both directions. While the test-retest systematically biased measurements of displacement and stiffness were −0.26 mm and 0.22 N/mm, respectively, and the bias of both parameters were in both directions. Conclusions The moderate-to-good inter-rater and test-retest reliabilities of the portable instrumented spinal stiffness assessment using a digital algometer and the Kinovea program by novice assessors were demonstrated in this study. Bland-Altman analysis showed that measuring stiffness was more stable and had less systematic bias than measuring displacement. To figure out how reliable the device is in general, more comprehensive studies should be comparatively conducted in the future on subgroups of patients with normal vertebra, hypomobile or hypermobile conditions.
Keywords: Spinal stiffness; Posterior anterior mobilization; Vertebral manipulation; Reliability